Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/adfm.201908641
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Light‐Emitting Electrochemical Cells with Nonpolymeric Materials

Abstract: Light-emitting electrochemical cells (LECs) have emerged as some of the simplest light-emitting devices. Indeed, numerous LECs have been produced using fluorescent polymers; however, initial LEC This article is protected by copyright. All rights reserved. 2structures require a mixture of polymers and electrolytes, thus strictly limiting their applicability. In contrast, recent advances in device technologies and material synthesis have opened a route for LECs using nonpolymeric materials. This progress report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 182 publications
(317 reference statements)
0
35
0
Order By: Relevance
“…[25] The second category of LECs uses ionic transition metal complexes (iTMC) as both the electronic and ionic conductor, with light emission occurring by phosphorescence originating from long-life triplet excitons. [26] Lee et al demonstrated the first iTMC-LEC using tris(bipyridine) ruthenium(II) hexafluorophosphate ([Ru(bpy) 3 ] (PF 6 ) 2 ), which produce orange-red light emission (Figure 3c). [27] An advantage of iTMC-LECs is the ability to change the color output through bandgap tuning by changing the metal center and ligand sphere.…”
Section: Introductionmentioning
confidence: 99%
“…[25] The second category of LECs uses ionic transition metal complexes (iTMC) as both the electronic and ionic conductor, with light emission occurring by phosphorescence originating from long-life triplet excitons. [26] Lee et al demonstrated the first iTMC-LEC using tris(bipyridine) ruthenium(II) hexafluorophosphate ([Ru(bpy) 3 ] (PF 6 ) 2 ), which produce orange-red light emission (Figure 3c). [27] An advantage of iTMC-LECs is the ability to change the color output through bandgap tuning by changing the metal center and ligand sphere.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, due to their simple and solution-processable device fabrication, compatibility with air-stable cathode metals, and low driving voltage, LECs are considered a promising alternative to traditional organic-light emitting diodes (OLEDs). [1][2][3] Such unique properties originate from the redistribution of the mobile ions near the electrodes under an external electrical field, which results in the electrochemical doping of the active layers and the formation of electrical double-layers (EDLs) and a dynamic p-i-n junction structure. 4,5 These doped layers reduced the carrier injection barriers and permitted easy charge injection causing low operating voltages using an inertmetal cathode.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although LECs possess several advantages over OLEDs, however, they suffer from low stability and long response time both of which are the most important features for LECs to become practical. 2,4,7,12 However various methods have been used to overcome these limitations. It was shown that the turn-on time (t on , time needed to reach the maximum brightness) of LECs was improved by the addition of ionic additives such as inorganic salts (LiPF 6 ) and ionic liquids with different ionic sizes and different intrinsic ionic conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…The emissive materials for LECs can be divided into several classes: conjugated polymers, [12] ionic transition metal complexes (iTMCs), [13,14] small molecules, [15] quantum dots (QDs), [16] and perovskites. [16,17] In spite of well-developed emissive materials and better device performance at the current stage, the organic LECs based on conjugated polymers, iTMCs and small molecules generally show broader electroluminescence (EL) spectra, which reduces the color saturation required for displays. To tailor the EL spectra from LECs, several optical techniques including interferometric filtering, [18,19] plasmonic filtering, [20,21] and energy down-conversion [22][23][24] have been employed.…”
Section: Introductionmentioning
confidence: 99%